Draft Annual Plan 1987-88 Volume II (Statistical Statement) Union Territory of Chandigarh - Planning Commission (Planning Commission, 1987)
Head of Development-Outlay Annual Plan Development Schemes/Project Outlay and Expenditure Draft Annual Plan 1987-88 Physical Targets and Achievement Draft Annual Plan 1987-88 Minimum Needs Programmes Draft Annual Plan 1987-88 Physical Targets and Achievements Draft Annual Plan 1987-88 Centrally Sponsored Schemes (Outlay and expenditure under central Sector only).
Planning and Evaluation Organisation Finance Department, Chandigarh Administration